Digital Humanities and the Common Good. The case of Entiendelo - Binotti, Lucia; Urioste Azcorra, Carmen (Revista de Humanidades Digitales, 2017)
Entiendelo. An App Helping Latin@s and their Advocates Navigate Stressful Linguistic and Cultural Situations is based on the idea that language should not be the last frontier to a good quality of life. The app contains three essential parts, all of them connected: 1) a glossary that aims to collect all Hispanic-American and US Latino variants of keywords associated with violence and healing, along with an urban dictionary that contains literary excerpts and authentic street sentences; 2) an interactive bilingual collection of inspirational quotes; 3) an interactive bilingual game, based on the model of Spent, where players are faced with the dilemmas of being a monolingual speaker in situations where their lack of diglossic dominance becomes a hindrance.